Effect of BTP2 on agonist‐induced vasoconstriction in the mouse aorta in vitro. (9th February 2021) - Zhou, Meng‐Yuan; Zhang, Li; Zheng, Dan‐Lin; Lai, Ying‐Yu; Liu, Pei‐Ming; Liu, Lin; Kuang, Su‐Juan; Yang, Hui; Rao, Fang; Long, Huang; Deng, Chun‐Yu
Abstract: BTP2 is a potent inhibitor of store‐operated Ca 2+ entry (SOCE), which plays a vital role in vasoconstriction. However, the direct effect of BTP2 on the contractile response remains unclear. Here, we investigated the effects and mechanisms of action of BTP2 in the mouse aorta. Isometric tension was measured using a Multi Myograph System with two stainless steel wires. Ca 2+ transient was recorded by confocal laser scanning microscope. The results showed that BTP2 markedly suppressed vasoconstriction mediated by SOCE and Ca 2+ influx mediated by SOCE. The cumulative concentration of BTP2 had no effect on the baseline of mouse aortic rings, whereas it increased vasoconstriction stimulated by 3 μmol/L Phenylephrine. BTP2 (1 μmol/L) significantly increased vasoconstriction induced by 3 μmol/L Phe or cumulative concentration. BTP2 also promoted noradrenaline‐induced aortic contraction. However, Phe‐ and noradrenaline‐induced contraction was not affected by 0.3 or 3 μmol/L BTP2, and BTP2 at 10 μmol/L significantly suppressed aortic contraction. BTP2 inhibited 5‐HT‐evoked contraction in a concentration‐dependent manner. BTP2 at higher concentrations (>3 μmol/L) inhibited CaCl2 ‐induced and 60 mmol/L K + ‐induced contraction with progressive reduction of maximal contraction in a concentration‐dependent manner. These results suggest that 1 μmol/L BTP2 increases contraction evoked by α1 adrenoreceptor activation. BTP2 at higher concentrations may inhibit Cav1.2 channels. Abstract : Phenylephrine‐induced contraction increased in the presence of 1 μmol/L BTP2, a potent inhibitor of store‐operated Ca 2+ entry (SOCE), whereas they were not affected by 0.3 or 3 μmol/L BTP2 and inhibited by 10 μmol/L BTP2.